Diagnosis of Obscure Gastrointestinal Bleeding - Satoshi Tanabe (Clinical Endoscopy, 2016)
Obscure gastrointestinal bleeding (OGIB) is defined as gastrointestinal bleeding from a source that cannot be identified on upper or lower gastrointestinal endoscopy. OGIB is considered an important indication for capsule endoscopy (CE). CE is particularly useful for the detection of vascular and small ulcerative lesions, conditions frequently associated with OGIB, particularly in Western countries. On the other hand, balloon enteroscopy (BE) can facilitate the diagnosis of lesions presenting with minimal changes of the mucosal surface, such as submucosal tumors, and can be used not only for diagnosis, but also for treatment, including endoscopic hemostasis. In other words, the complementary use of both CE and BE enables OGIB to be more efficiently diagnosed and treated. However, rebleeding can occur even in patients with negative results of CE, and such patients require repeat CE or BE. It is essential to effectively use both CE and BE based on a thorough understanding of the strong points and weak points of these procedures. Further advances and developments in virtual endoscopy incorporating computed tomography and magnetic resonance imaging are expected in the future.